2011
DOI: 10.1007/s00259-011-1938-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 18F-dopa PET/CT and 123I-MIBG scintigraphy in stage 3 and 4 neuroblastoma: a pilot study

Abstract: In our NB population (18)F-dopa PET/CT displayed higher overall accuracy than (123)I-MIBG scintigraphy. Consequently, we suggest (18)F-dopa PET/CT as a new opportunity for NB assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
88
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 110 publications
(91 citation statements)
references
References 33 publications
0
88
0
3
Order By: Relevance
“…The full texts of these 52 articles potentially eligible for inclusion were then reviewed and four were excluded as case series, eight because of possible data overlap and nine due to insufficient data to calculate sensitivity or specificity of [ 18 F]DOPA PET. The number of retrieved articles dealing with neuroblastoma [9,10] and ectopic adrenocorticotropin-secreting tumors [11] was not sufficient to perform a meta-analysis.…”
Section: Literature Searchmentioning
confidence: 99%
“…The full texts of these 52 articles potentially eligible for inclusion were then reviewed and four were excluded as case series, eight because of possible data overlap and nine due to insufficient data to calculate sensitivity or specificity of [ 18 F]DOPA PET. The number of retrieved articles dealing with neuroblastoma [9,10] and ectopic adrenocorticotropin-secreting tumors [11] was not sufficient to perform a meta-analysis.…”
Section: Literature Searchmentioning
confidence: 99%
“…When available and adequate, SPECT or SPECT/CT acquisitions can be obtained, although these modalities are time consuming, tend to cover only a limited field of view and increase the rate of patient sedation. Last but not least, a great variability in tumor uptake of 123 I-mIBG has been reported and false negative results may occur in 10-20 % of the cases [18]. 18 F-3,4-Dihydroxyphenylalanine (DOPA) is the radiolabelled analogue of DOPA, a precursor of dopamine and a precursor of catecholamines.…”
Section: Diagnostic Contextmentioning
confidence: 99%
“…The enzyme aromatic AA decarboxylase (AADC) is active in many neuroendocrine tumors, and metabolism of 18 F-FDOPA by AADC likely contributes to its favorable imaging properties because other system L substrates are not as effective for neuroendocrine tumor imaging (13). Of the neuroendocrine tumors, 18 F-FDOPA appears to best suited for imaging carcinoid tumors, pancreatic insulinomas, and neuroblastoma and can detect lesions not identified by CT, MR imaging, or other tracers used clinically for neuroendocrine tumor imaging (13,14). Studies comparing the utility of FDOPA with that of somatostatin receptor scintigraphy have demonstrated that somatostatin receptor scintigraphy typically demonstrates higher sensitivity for neuroendocrine tumor detection on a per-lesion basis, although 18 F- FDOPA can detect some neuroendocrine tumors that are not detected with somatostatin receptor scintigraphy (15,16).…”
Section: Neuroendocrine Tumorsmentioning
confidence: 99%